Southwest Bronze Age Culture in Lisbon city: the encosta de Sant’Ana vessel - Leitão, Vasco (2014)
This article presents the study of a ceramic vessel of the “Bronze do Sudoeste” culture (Southwest Bronze Age Culture) recovered during archaeological excavations in a settlement in Lisbon’s historical center. This vessel is related with several other occurrences from burials and/or ritual depositions in Southern Estremadura region during the first half of the 2nd millennium BC. The most ancient of these productions coexist with the last beaker vessels both in this region as in Southwest Portugal, according to the available radiocarbon data.